High performance broadband photodetectors based on Sb2Te3/n-Si heterostructure. (11th May 2020) - Zhang, Yuping; Tang, Libin; Teng, Kar Seng
Abstract: With the rapid development of optoelectronic devices, photodetectors have triggered unprecedented promise in the field of optical communication, environmental monitoring, biological imaging, chemical sensing. At the same time, there is a higher requirement for photodetectors. It is still a huge challenge for photodetectors that possess excellent performance, low cost and broad range photoresponse from ultraviolet to infrared. In this work, a facile, low cost growth of Sb2 Te3 thin film using magnetic sputtering was performed. After rapid annealing treatment, the crystallinity of the thin film was transformed from amorphous to polycrystalline. Ultraviolet-visible-infrared absorption study of the thin film revealed broad absorption range, which is ideal for use in broadband photodetectors. Such photodetectors can find many important applications in communication, data security, environmental monitoring and defense technology etc. A prototype photodetector, consisting of Sb2 Te3 /n-Si heterostructure, was produced and characterized. The device demonstrated a significant photoelectric response at a broad spectral range of between 250 and 2400 nm. The maximum responsivity and detectivity of the device were 270 A W −1 and 1.28 × 10 13 Jones, respectively, under 2400 nm illumination. Therefore, the results showed the potential use of Sb2 Te3 thin film in developing high performance broadband photodetectors.